Lack of Communication between Management and Employees - Serlange Campbell; Sharon Campbell-Phillips; Daneil Phillips (Budapest International Research and Critics University, 2020)
Communication is fundamental and vital to all administrative functions and communication is a means of transmitting information and making oneself understood by another or others, Sanchez & Guo (2005). Good communication skills are very important to ones success as an administrator, Yate (2009). This paper discusses how the lack of communication can affect production within organizations and provides guidelines on how both management and employees can create effectiveness by improving their communication skills. Various methods including surveys, questionnaires and interviews will be used through a descriptive research to generate the information that will guide the research. Person’s communication skills affect both personal and organisational effectiveness, Brun (2010); summers (2010). It seems reasonable to conclude that one of the most inhibiting forces to organisational effectiveness is a lack of effective communication, Lutgen-Sandvik (2010). The purpose of this study is to investigate the lack of communication between management and staff in different organizations. The objective is to identify the causes for miscommunication between management and staff, to investigate the kind of effects that the lack of communication would have on different organizations, to provide recommendations on improving the lack of communication, between management and staff throughout organizations.